Evaluation of the Use of Attitude Resources in the Undergraduate Studentsâ Argumentative Speech - Bella, Ivvon Septina; Mujiyanto, Januarius; Faridi, Abdurrachman (English Education Journal, 2018)
Appraisal Resources is the developmental theory of Hallidayâs interpersonal meaning proposing by Martin and White (2005) in which it evaluates the language meaning in the discourse. This study focused on attitude as a subsystem of appraisal resources. This study investigated comparison of the use of attitude between high and low ability students in argumentative speech. This study employed qualitative research in the form of spoken discourse analysis to examine 16 argumentative speeches within the framework of Appraisal Resources (Martin & White, 2005). The instruments applied Argumentative Speech Rubric adapted by Brown (2003) and Stevens and Levi (2005) to assess high and low ability as well as the appraisal resources checklist to determine the distribution of appraising items of attitude in high and low ability studentsâ argumentative speech, especially in affect, judgement, and appreciation as the subsystems of attitude. This study revealed that both high and low ability students were more dominant to use appreciation in their speeches. Thus, this study showed that speeches of high and low ability students were more appreciative than emotional or judgemental to align their personal voices in conveying their utterances and building strong persuasion through argumentative speech.